A Randomized Study of Comparison of the Incidence of Postoperative Hypocalcemia in Patients following Total Thyroidectomy versus Hemithyroidectomy - Baig, Maria; Javaid, Waqas (Biological and Clinical Sciences Research Journal, 2025)
Following thyroid surgery, hypocalcemia is a frequent side effect encountered. Total thyroidectomy is an evolution of prior techniques such as partial thyroidectomy and subtotal thyroidectomy. Objective: To compare the incidence of transient and permanent hypocalcemia in patients undergoing total thyroidectomy versus hemithyroidectomy. Methodology: This prospective randomized controlled trial was conducted over a 6-month period from January 1, 2024, to June 30, 2024, at the Department of ENT, Sir Ganga Ram Hospital, Lahore. 182 patients undergoing elective thyroid surgery for benign multinodular goiter were randomly allocated into two groups: Group A (n=91) underwent total thyroidectomy and Group B (n=91) underwent hemithyroidectomy. All procedures were performed by a same consultant ENT surgeon to eliminate operator-dependent variability. The primary outcome measure was the incidence of biochemical hypocalcemia (serum corrected calcium < 8.0 mg/dL) at 48 hours postoperatively. Secondary outcomes included the incidence of symptomatic hypocalcemia, rates of permanent hypocalcemia (persisting beyond 6 months), and postoperative parathyroid hormone (PTH) levels. Results: The incidence of biochemical hypocalcemia at 48 hours was significantly higher in Group A (Total Thyroidectomy) (38.5%, n=35) compared to Group B (Hemithyroidectomy) (5.5%, n=5) (p < 0.001). Symptomatic hypocalcemia occurred in 19.8% (n=18) of Group A patients and 2.2% (n=2) of Group B patients (p < 0.001). At the 6-month follow-up, permanent hypocalcemia was confirmed in 4.4% (n=4) of patients in Group A, while no cases (0%) were reported in Group B (p = 0.043). Mean postoperative PTH levels were significantly lower in Group A at both 48 hours and 6 months. Conclusion: Total thyroidectomy is associated with a significantly higher risk of both transient and permanent hypocalcemia compared to hemithyroidectomy. Meticulous surgical technique to preserve parathyroid function is paramount in total thyroidectomy. Preoperative counseling and postoperative monitoring for hypocalcemia are essential, particularly for patients undergoing total thyroidectomy.